2020
DOI: 10.1029/2019jb018652
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes of the Inner Core From Globally Distributed Repeating Earthquakes

Abstract: Time‐dependent travel times of seismic waves traversing the inner core from repeating earthquakes provided compelling evidence for an inner core differential motion. Here we conducted a systematic search for strong repeating earthquakes in the last three decades to examine the global pattern of temporal changes of the inner core. We performed extensive analyses on the quality of the repeating earthquakes and quantified the error (σic) of travel time measurements from all possible sources except the inner core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
(125 reference statements)
1
8
0
Order By: Relevance
“…We did make a few assumptions that the mantle influence in the ddt is small, that each local gradient is linear, and that the IC lateral shifts are from the rigid body rotation of the IC around the spin axis of the Earth, all of which seem reasonable. The new rate is also consistent with relatively low rates (0.05–0.10°/yr) in recent studies (Vidale, 2019; Yang & Song, 2020b) and remarkably close to the most recent estimate of 0.125°/yr from IC scattering waves by Wang and Vidale (2022). Such a slow rotation can also reconcile with a marginal rate of 0.13 ± 0.11°/yr from the normal‐mode data (Laske & Masters, 2003).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We did make a few assumptions that the mantle influence in the ddt is small, that each local gradient is linear, and that the IC lateral shifts are from the rigid body rotation of the IC around the spin axis of the Earth, all of which seem reasonable. The new rate is also consistent with relatively low rates (0.05–0.10°/yr) in recent studies (Vidale, 2019; Yang & Song, 2020b) and remarkably close to the most recent estimate of 0.125°/yr from IC scattering waves by Wang and Vidale (2022). Such a slow rotation can also reconcile with a marginal rate of 0.13 ± 0.11°/yr from the normal‐mode data (Laske & Masters, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…The IC temporal changes have been explained by an IC differential rotation that shifts laterally varying IC structures (Creager, 1997; Vidale, 2019; Vidale et al., 2000; Yang & Song, 2020b; Zhang et al., 2005). However, besides the driving force from the electromagnetic torque, the core‐mantle gravitational coupling tends to lock the IC at the position of gravitational equilibrium (Buffett, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…We need to clarify that the IC lateral gradient is not our "postulation," but a well-established observation reported by many previous studies (e.g., Creager, 1997;Song, 2000;Yang & Song, 2020b). The lateral velocity gradient is the dependence of travel time anomaly on the lateral sampling location.…”
Section: On the Local Velocity Gradient In The Inner Corementioning
confidence: 89%
“…While citing only the papers from their own group (Wen, 2006;Yao et al, 2015Yao et al, , 2019Yao et al, , 2021, TW23 ignored the disadvantageous evidence reported in many other studies, for example, to name a few: temporal changes of PKP DF (e.g, Song & Poupinet, 2007;Song & Richards, 1996;Sun et al, 2006;Yang & Song, 2020bZhang et al, 2005), inner-core scattering waves (e.g., Pang & Koper, 2022;Wang & Vidale, 2022), and antipodal PKIIKP arrivals (Tsuboi & Butler, 2020). Yang and Song (2020a) have systematically evaluated the temporal change of DF and CD with global doublets.…”
Section: Tw23 Did Not Consider a Large Body Of Evidence In Favor Of T...mentioning
confidence: 99%
See 1 more Smart Citation